Philippiniana Sacra. (Manila, Philippines : University of Santo Tomas, 1973)
Reponsible Parenthood: Sex Education/Manuel pinol, O.P.---pp. [573]-585.
Moral Perspectives in the Existentialism of Jean-Paul Sartre/Magin Borrajo, O.P.---pp.[531]-570.
Days of Obligation in the Philippines/Excelso Garcia,O.P.---pp.[583]-594.